2014
DOI: 10.1007/s11432-013-4881-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual image quality assessment metric using mutual information of Gabor features

Abstract: Information-based reduced reference image quality assessment incorporating non-tensor product wavelet filter banks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the absence of a perfect psychophysically defined error measure [34], for each quantized image, we report quantitive results under various perceptual metrics including the most popular mean squared error (MSE), structural similarity (SSIM) [35], Puzicha's spatial quantization error (SQE) [6] and the edge-aware spatial quantization error (ESQE) derived from our cost function. In the comparison, we set the dithering level in the Floyd Steinberg method to 1.0, the number of iterations in k-means to 10, and the number of iterations in MMC to 30.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of a perfect psychophysically defined error measure [34], for each quantized image, we report quantitive results under various perceptual metrics including the most popular mean squared error (MSE), structural similarity (SSIM) [35], Puzicha's spatial quantization error (SQE) [6] and the edge-aware spatial quantization error (ESQE) derived from our cost function. In the comparison, we set the dithering level in the Floyd Steinberg method to 1.0, the number of iterations in k-means to 10, and the number of iterations in MMC to 30.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been found that Gabor filters have excellent properties and the shapes of Gabor wavelets are similar to the receptive fields of simple cells in the primary visual cortex. Thus, visual features are extracted by 2D Gabor filter to reflect the nonlinear mechanism of HVS [18]. Instead of simulating the functional components of the low-level HVS, some high-level aspects of HVS, such as visual attention and visual saliency, are considered into feature extraction [9,19].…”
Section: Related Workmentioning
confidence: 99%
“…Local features extracting methods usually filter an image with a given operator, such as Gabor [7][8][9], Fourier transforms [10], Hough transforms [11], self-feedback template [12], LBP (Local Binary Pattern) [13][14], Wavelet [15][16] and other filters [17][18], etc. In [7], the authors used Log-Gabor filter to detect the edge-oriented urban characteristics, and two Log-Gabor filter response images to suppress the noise and acquire a smooth spatial region.…”
Section: Research Statusesmentioning
confidence: 99%